Pengaruh Perbandingan Daging Ayam dan Tepung Kecambah Kacang Merah (Phaseolus Vulgaris L.) terhadap Karakteristik Bakso - Ulyani, Arina; Wisaniyasa, Ni Wayan; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
This study aimed to determine the effect of the ratio of chicken meat and red bean sprouts flour to the characteristics of the meatballs and to determine the appropriate ratio of chicken meat and red bean sprouts flour to get the best meatball characteristic. Thisstudyused the completely randomized design, with ratio of chicken meat and red bean sprout flour treatmen consisted 5 level,namely (B0) 100% : 10%, (B1) 90% : 10%, (B2) 80% : 20%, (B3) 70% : 30%, (B4) 60% : 40%. Each treatment was repeated 3 times, in order to obtain 15 experimental units. The data obtained were using analysis of varianceandif thetreatmenthada significanteffect,itwascontinuedwiththe DuncanMultiple Range Test.The results showed that the ratio of chicken meat and red bean sprouts flour had an effect on moisture content, fat content, crude fiber content, texture, hedonic, aroma, taste, texture, and overall acceptance. And scoring on color, taste, and texture. The meatball with a ratio of chicken meat and red bean sprout flour of 90%: 10% was the best meatball characteristics with the criteria: water content of 68.86%, protein content of 23.22%, fat content of 8.03%, crude fiber content of 32.35 %, texture 6.63 N, color sensory test, aroma, taste, texture, and overall acceptance are liked.